Solid–Liquid Phase Transitions of Triglycerides in Griebenschmalz, Smalec, and Fedt Studied Using 13C Solid-State NMR with Dynamics-Based Spectral Filtering - Bernin, Diana; Leventaki, Emmanouela; Topgaard, Daniel (Applied Magnetic Resonance, 2023)
The consumer satisfaction of lard-based bread spreads depends on a delicate balance between a liquid fat phase, allowing the spread to flow, and solid fat crystals, providing the product with substance sometimes further enhanced by crispy pork cracklings. Here we apply 13C solid-state NMR with dynamics-based spectral filtering to characterize and follow the temperature dependence of the co-existing solid and liquid triglyceride phases in commercial German Griebenschmalz and Polish smalec, both containing cracklings, as well as home-made Danish fedt and, as a chemically more pure reference, German Schweineschmalz intended for baking. The NMR method allows detection of carbon atoms representative of saturated, unsaturated, and polyunsaturated acyl chains in both solid and liquid states. The results show that the solid comprises multiple crystal forms with different melting temperatures, while the liquid is at low temperature enriched in triglycerides with shorter acyl chains and higher degree of unsaturation, which become diluted with long-chain saturated triglycerides as the solids are melting. The obtained deeper understanding of the concomitant aspects of the phase transitions may pave the way for future efforts of rational optimization of fat blend composition to extend the temperature range over which the product contains sufficient amounts of both solids and liquids to give texture properties appealing to consumers.